Effect of N and K levels on growth, yield and nutrient uptake of FCV tobacco cv. Kanchan - KRISHNA, S KASTURI; REDDY, S V KRISHNA; KRISHNAMURTHY, V; RAO, C CHANDRASEKHARA; ANURADHA, M (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted during rabi, 2007-08 and 2008-09 at Jeelugumilli, Andhra Pradesh under irrigated Alfisols conditions to find out the effect of levels of nitrogen and potash on growth, yield and nutrient uptake pattern of flue-cured Virginia tobacco (Nicotiana tabacum L.) cv. Kanchan which is a heavy feeder and high yielder. The results of the experiment revealed that leaf dry weight increased from 30-90 days after planting with increase in N dose from 90 to 140 kg N/ha. Maximum accumulation of leaf dry weight was observed between 60-90 days after planting. Stem and root dry weight increased up to 120 days after planting during both the years. Green leaf yield and cured leaf yield increased progressively and significantly with increase in the N level from 90 to 140 kg N/ha. Higher grade index was recorded at 115 kg N/ha followed by 140 and 90 kg N/ha. The concentration of nitrogen in the leaf increased with increase in nitrogen dose but decreased with increase in level of potassium at the same nitrogen level. Nitrogen uptake increased with increased levels of N and K. Potassium content was high in the initial stages and slowly decreased with the advance in the age of the crop. Initially the difference in the uptake of N and K was narrow, the ratio widened with the age of the crop and finally the ratio was 1:1.3 to 1.4. Higher K uptake in leaf was observed at 115 kg N and while, higher K uptake in stem and root were observed at 140 kg N with 140 kg K2O /ha. The chemical quality parameters, viz. reducing sugars and nicotine in leaf lamina were within the acceptable limits. Higher green leaf yield, cured leaf yield, nitrogen and potassium uptake were recorded with application of 140 kg each of N and K2O/ha in FCV tobacco cv. Kanchan in irrigated Alfisols of Andhra Pradesh.